Offence of zina: the difficulties in its enforcement and the procedures / Ku Muniyatussaniah Ku Yahaya, Nadziatul Shazwani Nor Aman - Ku Yahaya, Ku Muniyatussaniah; Nor Aman, Nadziatul Shazwani (2005)
For the purpose of this study, we are focusing on the nature of zina offence whereby we are going to discuss on the procedures and methods to prove zina offence. This research will be looking into two different perspectives that is the perspective from the Islamic Hudud law and the present Syariah criminal law. Here, we have selected certain state enactments that is Syariah Criminal Offences (State of Selangor) Enactment 1995, Syariah Court Evidence (State of Selangor) Enactment 2003 and Syariah Criminal Offence (State of Kedah) Enactment 1988 as a comparison to the Islamic Hudud law. Besides, we will discuss a little bit on the punishment for zina offender if they are convicted for the charge of zina offences. There will be the statistics on zina cases from two states as an outcome from the law imposed that are the statistics in Selangor and statistics in Kedah on zina offence as well as attempted zina. These statistics are to show the number of zina cases been dealt by the court in the respective states which is contradict to the real numbers of zina offence committed. This is due to the said rigidity of procedures and methods as laid down in the Holy Quran and Hadith, as well as adopted by the present Syariah law. As a conclusion, we have the answer on why there is not much effort put in convicting zina offender because the procedures is too rigid and many cases have been dismissed by the courts as the evidence cannot be established.